International Conference on Biomedical Engineering (ICoBE-2012) - Anon (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Biomedical Engineering (ICOBE-2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th February 2012 at Bayview Beach Resort, Penang, Malaysia.